2014
DOI: 10.6018/analesps.30.2.159261
|View full text |Cite
|
Sign up to set email alerts
|

Conciencia emocional, estados de ánimo e indicadores de ajuste individual y social en niños de 8-12 años

Abstract: Resumen: La conciencia emocional o experiencia consciente de la emoción es un concepto clave relacionado con diferentes indicadores de ajuste individual del menor, como las quejas somáticas. Esta relación, mediatizada por los estados de ánimo, se ha demostrado en población preadolescente y adolescente. Sin embargo, apenas se ha analizado en franjas de edad más bajas e incluyendo otros indicadores de ajuste a diferentes contextos, como la adaptación. Por ello, el objetivo de este trabajo es el de analizar la co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
2
3
0
5
Order By: Relevance
“…We examined the three dimensions of EI proposed by Salovey and Mayer [ 70 ], and also the different dimensions of empathy (i.e., perspective-taking, empathetic understanding, empathic stress, and empathetic joy). In general, the results of this study regarding cyberaggressors indicated the existence of a relationship between low empathy and low emotion regulation with aggressive behavior against peers, with this finding coinciding with the results of previous research [ 71 , 72 , 73 ].…”
Section: Discussionsupporting
confidence: 91%
“…We examined the three dimensions of EI proposed by Salovey and Mayer [ 70 ], and also the different dimensions of empathy (i.e., perspective-taking, empathetic understanding, empathic stress, and empathetic joy). In general, the results of this study regarding cyberaggressors indicated the existence of a relationship between low empathy and low emotion regulation with aggressive behavior against peers, with this finding coinciding with the results of previous research [ 71 , 72 , 73 ].…”
Section: Discussionsupporting
confidence: 91%
“…Those with more aggressive behaviour are clearly more likely to become bullies, and those who are more shy are more likely to become victims. In addition, some studies suggest that a good deal of bullying problems may be caused by poor emotional management [36]. In this sense, it is considered that EI could become a protective variable against bullying.…”
Section: Peer-to-peer Harassmentmentioning
confidence: 99%
“…In recent years, there has been an increase of interest in the role played by emotion regulation in the explanation of some problems of psychosocial school adjustment (Adrian, Zeman, & Veits, 2011; Humphrey, Curran, Morris, Farrell, & Woods, 2007). In fact, some authors have suggested that a large part of the problems of violence could originate in the deficient self-regulation of emotions (Villanueva, Prado-Gascó, González, & Montoya, 2014). Accordingly, the benefits of social and emotional learning (SEL) interventions have been corroborated in recent studies (Taylor, Oberle, Durlak, & Weissberg, 2017), indicating the enhancement of students’ behavioral adjustment in the form of increased prosocial behaviors and reduced conduct problems (Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, 2011).…”
mentioning
confidence: 99%